2021
DOI: 10.1101/2021.11.05.21265900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parents’ intention to vaccinate their 5-11 years old children with the COVID-19 vaccine: rates, predictors and the role of incentives

Abstract: BackgroundOn September 20, 2021, Pfizer announced encouraging effectiveness and safety results from their COVID-19 vaccine clinical trials in 5-11 years old children. This study aims to assess parents’ perceptions and intention to vaccinate their 5-11 years old children and to determine the socio-demographic, health-related and behavioral factors, as well as the role of incentives beyond these factors, in predicting this intention.MethodsA cross-sectional representative online survey among parents of children … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…Regional and international studies reported lower rates in some areas, including 35% in Qatar and 33% in Chicago ( 18 , 20 ), however, these percentages included parents with children >11 years of age, which may explain the differences ( 18 , 20 , 23 , 24 , 30 ). A preprint from Israel including parents with 5–11-year-old children, similar to our population, reported that 43% of these parents were hesitant to vaccinate their children ( 31 ). In July 2021, a small study conducted in Arkansas found that around 30% of parents will not vaccinate their children or only vaccinate them when required; interestingly, the hesitancy rates among parents of 12–18-year-old children were similar to the rate among parents with children younger than 12 years of age (28 and 27%, respectively) ( 32 ).…”
Section: Discussionsupporting
confidence: 57%
“…Regional and international studies reported lower rates in some areas, including 35% in Qatar and 33% in Chicago ( 18 , 20 ), however, these percentages included parents with children >11 years of age, which may explain the differences ( 18 , 20 , 23 , 24 , 30 ). A preprint from Israel including parents with 5–11-year-old children, similar to our population, reported that 43% of these parents were hesitant to vaccinate their children ( 31 ). In July 2021, a small study conducted in Arkansas found that around 30% of parents will not vaccinate their children or only vaccinate them when required; interestingly, the hesitancy rates among parents of 12–18-year-old children were similar to the rate among parents with children younger than 12 years of age (28 and 27%, respectively) ( 32 ).…”
Section: Discussionsupporting
confidence: 57%
“…However, caregivers are reluctant to vaccinate their young child due to long-term vaccine safety concerns. Reports from an Israeli study and the Kaiser Family Foundation (KFF) [23,26] performed on similar age groups found an acceptance rate of 45% and 46%, respectively, 10% higher than our study.…”
Section: Baseline Description Of Vaccine Uptake Caregivers' Acceptanc...contrasting
confidence: 82%
“… Yes [Y], unsure [U], no [N] Yes: 74.0 Unsure: 14.0 No: 12.0 ( McKinnon et al, 2021 ) If a COVID-19 vaccine is available, will you vaccinate your child? Very likely [Y], somewhat likely [U], unlikely [N] Yes: 73.3 Unsure: 14.3 No: 12.4 ( Shmueli, 2021 ) How appropriate do you consider to vaccinate your children against COVID-19? A scale from 1 [not appropriate at all] to 6 [very appropriate, Y] Yes: 57.2 Unsure: NR No: NR NR: not reported.…”
Section: Resultsmentioning
confidence: 99%